1986
DOI: 10.2134/agronj1986.00021962007800040032x
|View full text |Cite
|
Sign up to set email alerts
|

Dryland Grain Sorghum Water Use, Light Interception, and Growth Responses to Planting Geometry1

Abstract: Crop yields are primarily water-limited under dry land production systems in semiarid regions. This study was conducted to determine whether the growing season water balance could be manipulated through planting geometry. The effects of row spacing, row direction, and plant population on the water use, light interception, and growth of grain sorghum (Sorghum bico/or (L.) Moench] were investigated at Bushland, TX, on a Pullman clay loam (fine, mixed, thermic Torrertic Paleustoll). In 1983, which had a dry growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 9 publications
(13 reference statements)
5
46
0
1
Order By: Relevance
“…The current study was in confirmation of number of grains per head playing a major contributive role towards grain yield of sorghum. ) but significantly higher than the grain yield (2433 kg ha -1 ) obtained from row spacing at 60 cm apart (Table 1).Similar response to row spacing has been reported in previous studies where similar row spacing produced higher yields of sorghum grains (Stickler & Laude, 1960;Steiner, 1986), forage (Stickler & Laude, 1960) and other crops such as soybean (De Bruin & Pedersen, 2008). Higher biomass production of sorghum crop with a narrower row spacing of 19cm has been mentioned by Snider et al (2012), and the phenomenon might be due to the better light interception (Steiner, 1986) and decreased inter-row competition between pants (De Bruin & Pederson, 2008).…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…The current study was in confirmation of number of grains per head playing a major contributive role towards grain yield of sorghum. ) but significantly higher than the grain yield (2433 kg ha -1 ) obtained from row spacing at 60 cm apart (Table 1).Similar response to row spacing has been reported in previous studies where similar row spacing produced higher yields of sorghum grains (Stickler & Laude, 1960;Steiner, 1986), forage (Stickler & Laude, 1960) and other crops such as soybean (De Bruin & Pedersen, 2008). Higher biomass production of sorghum crop with a narrower row spacing of 19cm has been mentioned by Snider et al (2012), and the phenomenon might be due to the better light interception (Steiner, 1986) and decreased inter-row competition between pants (De Bruin & Pederson, 2008).…”
Section: Methodssupporting
confidence: 85%
“…Narrow row spacing results in higher grain yields in soybean (De Bruin & Pederson, 2008) and in other crops (Stickler & Laude, 1960). Narrow row spacing resulting in higher yield is explained by the improved light interception (Steiner, 1986) and decreased plant to plant competition between plants (De Bruin & Pederson, 2008). Johnson et al (2005) reported reduction in total weed density in 30cm apart rows of peanut (Arachis hypogea) as compared to the weed density at greater spacing.…”
mentioning
confidence: 99%
“…Physical water use efficiency with respect to total biomass of sweet sorghum and total water input was in the range of 3.8 to 15.6 kg m -3 with an average of 8.3 kg m -3 , and these values are greater than that of the WUE values reported by other researchers (Steiner, 1986;Mastrorilli et al, 1999;Patil, 2007;Wani et al, 2012). In comparison to sweet sorghum, water productivity of sugarcane is in the range of 3.8 to 18.4 kg m -3 (Thompson, 1976;Robertson and Muchow, 1994;Kingston, 1994;Olivier and Singels, 2003;Bahrani et al 2008;Wiedenfeld and Enciso, 2008).…”
Section: Water Use Efficiencymentioning
confidence: 54%
“…Steiner [50,51] showed that for a 0.76-m row width planting of a sorghum crop in Bushland, row orientation affected light interception with N-S rows intercepting more radiation and having smaller net radiation versus E-W rows. These observations tend to indicate that, in terms of radiation, N-S row orientation may result in smaller E compared to E-W row orientation.…”
Section: Diel Dynamics Of Ementioning
confidence: 99%